Impairment of force development in K(ATP) channel deficient skeletal muscle involves calcium ion influx through L-type calcium ion channels - Cifelli, Carlo (University of Ottawa (Canada), 2006)
ATP-sensitive potassium (KATP) channels link membrane excitability to metabolism. They are regulated by intracellular nucleotides and other factors, and have been shown to play a role in development of skeletal muscle force, but controversy surrounds their role during fatigue. The aim of this research project was to determine the role of KATP channel under conditions that allow for better assessment of changes in force during fatigue, by virtue of using a smaller whole muscle model less subject to anoxia. Thus, the first objective was to determine the effect of the loss of KATP channel activity on force during fatigue in small FDB muscle bundles. KATP channel deficient fibers had faster and greater decreases in peak tetanic force during fatigue, developed greater resting tension, and had lower force recovery following fatigue compared to control wild type muscles. The second objective was to determine whether the functional impairment in skeletal muscle without KATP channel activity was due to an increase in Ca 2+ influx. When [Ca2+]e was reduced or L-type Ca2+ channels partially blocked, Kir6.2-/- FDB muscle had slower fatigue development, less resting tension, and had an improved force recovery. A novel phenomenon was observed while studying the effect of KATP channel activity in vitro. During a second bout of fatigue the decrease in peak tension was significantly lower than the decrease during the first bout of fatigue. Furthermore, the deleterious effects of the loss of KATP channel activity during an initial fatigue were absent during the second fatigue in FDB exposed to glibenclamide. It is concluded (i) that the KATP channel is important to prevent impairment of function during fatigue, (ii) that this impairment of function is due to an increase in Ca2+ influx through L-type Ca2+ channels, causing Ca2+ overload, and (iii) that fatigue resistance increases while the dependency on the KATP channel to prevent function impairment and fiber damage decreases following one fatigue bout at 37°C; a phenomenon here termed fatigue pre-conditioning.
Keywords: Biology, Molecular.; Biology, Cell.